Posterior reversible encephalopathy syndrome: a rare case with delayed reverse - Islam, Ahmed Tanjimul; Uddin, Md Kafil; Ali, Md Ahmed; Kundu, Pijush Kumar; Alahi, Md Munzur; Amin, Md Parvez; Sarkar, Mukul Kumar (BIRDEM Medical Journal, 2019)
Posterior reversible encephalopathy syndrome (PRES) is a reversible phenomenon diagnosed with both clinical and radiological criteria. We present anatypical case of PRES with unusual delayed reversal. A 29-year-old female presented withseizure and altered consciousness during post-partum periods. The initial computed tomographyscan of brain was normal. But subsequent magnetic resonance imaging of brain showed hyperintense lesion in rightparieto-occipital region. After 7 weeks of multidisciplinary team effort, the patient recovered both clinically and radiologically. High index of suspicion with long term follow up is crucial for this curable and reversible syndrome. Because of rarity in delayed recovery, this case of PRES is reported. Birdem Med J 2019; 9(3): 248-250